Na2SnO3 as a novel anode for high performance lithium storage and its electrochemical reaction mechanism. (20th August 2019) - Lu, Fan; Zeng, Weiying; Lin, Haifeng; Liu, Shengzhou; Tian, Xiaoqing; Yang, Jie; Li, Jumei; Yang, Yin
Abstract: Herein, Na2 SnO3 is employed as an anode for rechargeable lithium ion battery (LIB). We thoroughly investigated the electrochemical performance of Na2 SnO3 in comparison with the most commonly used Sn based oxides, such as SnO2 and Li2 SnO3 . It is found that Na2 SnO3 is greatly superior to SnO2 and Li2 SnO3 in terms of capacity, cycling stability and rate capability. Impressively, Na2 SnO3 presents favorable specific capacity of 480 mA h g −1 at current density of 200 mA g −1 after 100 cycles and still delivers a capacity of 439 mA h g −1 at extremely large current density of 1000 mA g −1, which are leading the performance in anodes for LIBs. Ex situ SEM analysis of anodes after different cycles revealed the surface microstructure of anodes plays a critical role in determining cycling stability. The SEM results show big cracks on the surface of electrode for SnO2 after less 15 cycles and for Li2 SnO3 after more 100 cycles, resulting from their severe volume change during charging-discharging process. However, Na2 SnO3 electrode exhibits uniform surface morphology after 100 cycles. It is concluded the "Na2 O″ intrinsic matrix of Na2 SnO3 combining with "Li2 O″ formed from the conversion reaction can act as a mixture buffering matrix that contributes to keeping the electrochemically formed nanoscale Sn particles apart and preventing their agglomeration during Li−Sn alloy formation and decomposition, thus inhibiting the volume expansion and the capacity fading by maintaining the electrode integrity. In addition, the electrochemical reaction mechanism of Na2 SnO3 with Li is investigated by ex situ XRD technique. The findings in this study provide a new valuable anode for high-performance LIBs and an insightful viewpoint of developing anode materials with high electrochemical performance by introducing the electrochemical inactive intrinsic matrix. Highlights: Na2 SnO3 was employed as anode material for LIBs. Na2 SnO3 showed outstanding cycling stability due to the synergetic effect of "Na2 O″ intrinsic matrix and "Li2 O″ extrinsic matrix. Na2 SnO3 showed dramatically enhanced electrochemical performance in terms of capacity, cycling stability and rate capability in comparison to SnO2 and Li2 SnO3. The electrochemical reaction mechanism of Na2 SnO3 with Li was investigated by ex situ XRD technique.